Distribution and population density of Tarsius bancanus borneanus in secondary and rehabilitated forests of Universiti Putra Malaysia Bintulu Sarawak campus - Muhd Sahimi, Hani Nabilia; Chubo, John Keen; Saripuddin, Noor Bahiah; Mohd Top @ Mohd Tah, Marina (2015)
Tarsius bancanus borneanus was first acknowledge by Elliot in 1990. This sub-species can be found in the Borneo Island which consists of Sabah and Sarawak of Malaysia, Brunei Darussalam and Kalimantan, Indonesia. Tarsius bancanus borneanus is endemic to Borneo and has been listed as a Totally Protected Animal under the Wildlife Ordinance 1998 of Sarawak. According to the IUCN, Tarsius bancanus borneanus population is now decreasing and it has been listed as a vulnerable species. The present study was conducted in Universiti Putra Malaysia Bintulu Sarawak Campus (UPMKB), from October 2014 until January 2015. Through observations and capture-effort sampling covering an area of 18.75 ha secondary forest patches and 7.13 ha of rehabilitated forest, a total of 13 tarsier were captured using mist nets, three were recorded through observation and one tarsier recaptured. The population density of tarsiers in the secondary forest was 0.75 individuals per ha while 0.28 individuals per ha was recorded for the rehabilitated forest. By using the captured per unit effort (net-hours) method, the average time of tarsiers being captured in the secondary forest patches was 30.55 nets-hour/animal and 24 nets-hour/animal in the rehabilitated forest. The sex ratio of male to female of captured tarsier was 9:4. The present results provide data on the presence of tarsier in both the secondary and rehabilitated forest mainly in UPMKB campus thus highlighting the conservation value of those forest areas.